6 Reducing unnecessary patient isolation on general medicine units. (2nd December 2020) - Carson, Joseph; Taabazuing, Mary-Margaret; Sider, Cody; Payne, Michael; Behzadian, Yassmin; Newman, Alice; Gutierrez, Elaine Hunter; Elliot, Linda; Devoe, Brittany
Abstract : Background: Droplet+contact (DC) precautions are used to prevent the spread of acute respiratory infections. Clinicians at London Health Sciences Centre, an academic tertiary care organization in Ontario, Canada, have reported that many patients remain isolated longer than necessary. Research suggests that prolonged isolation may negatively impact patient outcomes, experience, and costs. Objectives: Reduce unnecessary DC precautions on general medicine units by 30% by March 31, 2020. Methods: Our multi-disciplinary team designed this project using the Model for Improvement. We identified barriers to precaution removal through surveys, chart reviews, process mapping (figure 1 ), and fishbone diagramming (figure 2 ). Our change drivers focussed on motivation, precaution identification, reassessment cues, and standardized decision-making (figure 3 ). In a series of PDSA cycles, we tested and implemented new discontinuation criteria and a decision-support tool across two hospitals (figure 4 ). Outcomes measures were: (1) % unnecessary DC precautions, collected by weekly physician audits, and (2) DC precautions lasting >5 days, collected from electronic medical records. Our process measures were: (1) user test fidelity, and (2) physician awareness. Our balance measure was physician satisfaction with new criteria. Statistical analysis was performed using Student's t-test, run charts, and process control charts (QI Macros, IHI Rules). Results: We completed eight appropriateness audits (n=212 patients) at two hospitals between December 2019 – March 2020. During user testing, eight physicians applied the new criteria and decision-support tool to five mock cases at 92% (37/40) fidelity. After implementing changes, mean precaution appropriateness increased from 30% (24/80) to 64% (85/132), (p<0.001). Out of 35 physicians surveyed, 22 (63%) were aware of new criteria; of those, 19 (86%) found the new criteria useful. However, there was no special-cause variation in DC precautions >5 days. Conclusions: Discontinuing prolonged DC precautions is important to conserve vital resources, especially during the COVID-19 pandemic. We reduced these incidents by implementing standard discontinuation criteria and a decision support tool. Our next step is to adapt these tools to standardize precaution removal for COVID-19 patients.